Method for removing plastics from water bodies using biobased composite membranes
Patent Information
- Application Number
- CN202611193502.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-07
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2046-08-07
AI Technical Summary
公开号为CN 120819006 A的发明专利公开了一种过滤纳米塑料的阳离子化复合纸基材料的制备方法及其应用,但该制备方法需要使用低共熔溶剂、硅烷偶联剂、聚偏氟乙烯、聚乙烯亚胺等多种材料,合成过程繁琐复杂
[0024]1、本发明的生物基复合膜去除水体塑料的方法,使生物基复合膜对塑料保持高去除率的同时,还能够维持较高的水通量,实现了水体中塑料的高效净化。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of environmental protection and water treatment technology, and specifically relates to a method for removing plastics from water using a bio-based composite membrane. Background Technology
[0002] In recent years, microplastics (plastic particles with a diameter between 1 μm and 5 mm) and nanoplastics (plastic particles with a diameter less than 1 μm) have been widely detected in drinking water sources around the world. The sources of microplastics and nanoplastics in drinking water exhibit significant complexity and regional differences, making their removal technologies increasingly important. In current water treatment applications, membrane filtration technology based on physical retention is a relatively mature method for removing microplastics and nanoplastics, and it is easily compatible with existing water treatment processes.
[0003] Recent research has reported some progress in removing plastics from water using cellulose-based materials. However, existing processes still face bottlenecks such as large quantities of cellulose-based materials, complex synthesis processes, poor removal efficiency of nanoplastics, and low water flux. For example, invention patent CN 118223330 A discloses a method for preparing and applying a composite paper-based material for filtering micro / nanoplastics. This method combines nanocellulose with filter paper fibers via glutaraldehyde crosslinking to obtain a nanocellulose / filter paper composite paper. When used to remove 100 nm micro / nanoplastics, the removal rate was only 21.4%, with a maximum water flux of 704.6 L / m³. -2 h -1 bar -1 Chinese invention patent CN 120819006 A discloses a method for preparing a cationized composite paper-based material for filtering nanoplastics and its application. However, this preparation method requires the use of multiple materials such as a eutectic solvent, silane coupling agent, polyvinylidene fluoride, and polyethyleneimine, making the synthesis process cumbersome and complex. The cationized composite paper-based material achieves a maximum removal rate of 97.56% for 100 nm plastics, but its water flux is only 1890 L / m³. -2 h -1 bar -1 However, existing technologies for removing microplastics and nanoplastics based on cellulose-based materials cannot achieve both high water flux and high removal rate. Patent CN 121155374 A discloses a method for preparing a Janus-type separation membrane based on nanocellulose. This method involves complex processes such as electrospinning, spraying, and crosslinking. The Janus-type separation membrane achieves a removal rate of less than 80% for 100 nm plastics. In summary, existing technologies for removing microplastics and nanoplastics based on cellulose-based materials suffer from the problem of simultaneously achieving high removal efficiency and high water flux. Summary of the Invention
[0004] In view of the shortcomings of the prior art, the purpose of this invention is to provide a method for removing plastics from water using a bio-based composite membrane. This method significantly improves the removal rate and water flux of microplastics and nanoplastics, and effectively avoids secondary environmental pollution.
[0005] The objective of this invention is achieved through the following technical solution.
[0006] A method for removing plastic from water using a bio-based composite membrane includes: filtering a plastic aqueous dispersion through a bio-based composite membrane under conditions of -0.1 to -0.08 MPa, wherein the preparation method of the bio-based composite membrane includes the following steps:
[0007] Step 1: Prepare a first cellulose-based nanomaterial ultrasonic dispersion, which is a homogeneous mixture of cellulose-based nanomaterials and water.
[0008] Step 2: Under conditions of -0.1 to -0.08 MPa, the cellulose-based nanomaterials in the ultrasonic dispersion of the first cellulose-based nanomaterials are retained on the cellulose acetate membrane by vacuum filtration to obtain a composite membrane, wherein the cellulose-based nanomaterials in the ultrasonic dispersion of the first cellulose-based nanomaterials form a first fiber layer on the cellulose acetate membrane;
[0009] Step 3: Prepare a second cellulose-based nanomaterial ultrasonic dispersion, which is a homogeneous mixture of cellulose-based nanomaterials and water. Under conditions of -0.1 to -0.08 MPa, filter the cellulose-based nanomaterials in the second cellulose-based nanomaterial ultrasonic dispersion onto the first fiber layer of the composite membrane to form a second fiber layer, thus obtaining a bio-based composite membrane. The ratio of cellulose-based nanomaterials in the first cellulose-based nanomaterial ultrasonic dispersion to that in the second cellulose-based nanomaterial ultrasonic dispersion is (0.1~0.2):(0.1~0.2) by mass.
[0010] The theoretical loading of cellulose-based nanomaterials in the first fiber layer = m1 / S, where m1 is the mass of cellulose-based nanomaterials in the ultrasonic dispersion of the first cellulose-based nanomaterials, and S is the effective filtration area of the vacuum filtration.
[0011] The theoretical loading of cellulose-based nanomaterials in the second fiber layer = m2 / S, where m2 is the mass of cellulose-based nanomaterials in the ultrasonic dispersion of the second cellulose-based nanomaterials;
[0012] The theoretical loading of cellulose-based nanomaterials in the first fiber layer and the sum of the theoretical loading of cellulose-based nanomaterials in the second fiber layer are 0.08~0.12 mg cm⁻¹. -2 ;
[0013] The concentrations of cellulose-based nanomaterials in the first and second ultrasonic dispersions of cellulose-based nanomaterials are both 0.05~0.2wt%, the length of the cellulose-based nanomaterials is 1~30 μm, and the diameter of the cellulose-based nanomaterials is 1~50 nm.
[0014] In the above technical solution, cellulose-based nanomaterials include: cellulose nanofibers.
[0015] In the above technical solution, the pore size of the cellulose acetate membrane is 4.75~5.25 μm, and the diameter of the cellulose acetate membrane is 24.8~25.2 mm.
[0016] In the above technical solution, the effective filtration area (S) of the vacuum filtration is 1.54~2.01 cm². 2 .
[0017] In the above technical solutions, the methods for preparing the first cellulose-based nanomaterial ultrasonic dispersion and the second cellulose-based nanomaterial ultrasonic dispersion are the same, both including: mixing the cellulose nanofiber dispersion with water and ultrasonicating to mix them evenly.
[0018] In the above technical solution, the ultrasound duration is 50-60 min and the ultrasound frequency is 38-42 kHz.
[0019] In the above technical solution, the plastic aqueous dispersion includes: plastic and water, wherein the plastic is microplastic and / or nanoplastic.
[0020] In the above technical solution, the plastic material is polystyrene.
[0021] In the above technical solution, the concentration of plastic in the plastic aqueous dispersion is 10~50 mg / L.
[0022] In the above technical solution, the plastic aqueous dispersion is subjected to air flotation treatment before filtration.
[0023] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0024] 1. The method for removing plastics from water using a bio-based composite membrane of the present invention enables the bio-based composite membrane to maintain a high removal rate of plastics while also maintaining a high water flux, thereby achieving efficient purification of plastics in water.
[0025] 2. Before filtration, the plastic aqueous dispersion is subjected to air flotation treatment. The combination of bio-based composite membrane and air flotation can further improve the purification effect of plastic in water.
[0026] 3. The preparation process of the bio-based composite membrane of the present invention uses inexpensive and readily available biodegradable materials, which will not generate secondary pollution or difficult-to-treat waste; and the cost is low, so it can be applied on a large scale to the purification of drinking water or sewage. Detailed Implementation
[0027] The technical solution of the present invention will be further described in detail below with reference to the embodiments.
[0028] In the following examples, polystyrene nanoplastics (100 nm in diameter) and polystyrene microplastics (1 μm in diameter) were both purchased from Nantong Zhichuan Microsphere Biotechnology Co., Ltd.
[0029] The cellulose acetate membrane (pore size 5 μm, diameter 25 mm) was purchased from Haining Delu New Material Technology Co., Ltd.
[0030] The cellulose nanofiber dispersion was purchased from Songhu Shenjian Technology (Dongguan) Co., Ltd. The cellulose nanofiber dispersion is a mixture of cellulose nanofibers (the length of the cellulose nanofibers is 1~30 μm and the diameter of the cellulose nanofibers is 1~50 nm) and water. The concentration of cellulose nanofibers in the cellulose nanofiber dispersion is 2wt%, and the surface groups of the cellulose nanofibers are hydroxyl groups (-OH).
[0031] Examples 1-5
[0032] A method for preparing a bio-based composite membrane includes the following steps:
[0033] Step 1: The cellulose nanofiber dispersion is uniformly dispersed in deionized water and sonicated at 40 kHz for 60 min (ultrasound power is 360 W) to mix evenly, so as to obtain a uniformly dispersed first cellulose-based nanomaterial ultrasonic dispersion with a concentration of 0.05 wt% in the first cellulose-based nanomaterial ultrasonic dispersion.
[0034] Step 2: Install the cellulose acetate membrane onto the glass filter (the effective filtration area (S) of the glass filter is 1.77 cm²). 2 Under -0.09 MPa conditions, cellulose nanofibers in M mL of the ultrasonic dispersion of the first cellulose-based nanomaterials were trapped on the cellulose acetate membrane by vacuum filtration to obtain a composite membrane, wherein the cellulose nanofibers in the ultrasonic dispersion of the first cellulose-based nanomaterials formed a first fiber layer on the cellulose acetate membrane.
[0035] Step 3, prepare the second cellulose-based nanomaterial ultrasonic dispersion: Disperse the cellulose nanofiber dispersion uniformly in deionized water, and sonicate at 40 kHz for 60 min (ultrasound power 360 W) to mix evenly, obtaining a uniformly dispersed second cellulose-based nanomaterial ultrasonic dispersion. The concentration of cellulose nanofibers in the second cellulose-based nanomaterial ultrasonic dispersion is 0.05 wt%.
[0036] Under -0.09 MPa conditions, cellulose nanofibers in N mL of the second cellulose-based nanomaterial ultrasonic dispersion were trapped on the first fiber layer of the composite membrane by vacuum filtration to form the second fiber layer, thus obtaining a bio-based composite membrane with a bilayer structure. The ratio of cellulose nanofibers in the first cellulose-based nanomaterial ultrasonic dispersion to cellulose nanofibers in the second cellulose-based nanomaterial ultrasonic dispersion is X by mass fraction.
[0037] The bilayer structure of the bio-based composite membranes obtained in Examples 1-5 consists of a first fiber layer and a second fiber layer arranged from bottom to top. The theoretical loading of cellulose nanofibers in each fiber layer (either the first or second fiber layer) is calculated as follows: Theoretical loading of cellulose nanofibers in the first fiber layer = ρ × M × concentration of cellulose nanofibers in the ultrasonic dispersion of the first cellulose-based nanomaterial / S = m1 / S (where m1 is the mass of the cellulose-based nanomaterial in the ultrasonic dispersion of the first cellulose-based nanomaterial); Theoretical loading of cellulose nanofibers in the second fiber layer = ρ × N × concentration of cellulose nanofibers in the ultrasonic dispersion of the second cellulose-based nanomaterial / S = m2 / S (where m2 is the mass of the cellulose-based nanomaterial in the ultrasonic dispersion of the second cellulose-based nanomaterial). Where ρ is 1000 mg / cm³. 3 The theoretical loading of all cellulose nanofibers on the bio-based composite membrane (total theoretical loading of cellulose nanofibers on the bio-based composite membrane) = theoretical loading of cellulose nanofibers in the first fiber layer + theoretical loading of cellulose nanofibers in the second fiber layer.
[0038] A method for removing plastic from water using a bio-based composite membrane includes: filtering 5 mL of a plastic aqueous dispersion through the bio-based composite membrane under -0.09 MPa conditions to obtain filtrate and recording the filtration time t (in hours); determining the concentration C1 of the plastic in the filtrate using an ultraviolet spectrophotometer (model UV-1601, purchased from Beijing Beifen Ruili Analytical Instruments (Group) Co., Ltd.), and calculating the plastic removal rate and water flux. The bio-based composite membrane is one of the bio-based composite membranes obtained in Examples 1-5; the plastic aqueous dispersion is a mixture of polystyrene nanoplastics and deionized water, and the concentration C0 of the polystyrene nanoplastics in the plastic aqueous dispersion is 10 mg / L.
[0039] Removal rate (%) = (C0 - C1) / C0;
[0040] Water flux (F) = V / (S × t × P);
[0041] Where S is the effective filtration area (1.77 cm²). 2 P is the negative pressure during the filtration process (0.09 MPa, i.e., 0.9 bar), V is the volume of the plastic aqueous dispersion (5 mL), t is the filtration time (h), and F is the water flux (L m). -2 h -1 bar -1 ).
[0042] The removal rate, water flux, M, N, X, theoretical loading of cellulose nanofibers in the first fiber layer, and theoretical loading of cellulose nanofibers in the second fiber layer of the bio-based composite membranes obtained in Examples 1-5 are shown in Table 1.
[0043] Table 1
[0044]
[0045] As shown in Table 1, the total theoretical loading of cellulose nanofibers on the bio-based composite membrane obtained in Example 1 is only 0.098 mg cm⁻¹. -2 It achieved a removal rate of 94.0% for polystyrene nanoplastics with a diameter of 100 nm, with a water flux of 10766.0 L / m³. -2 h -1 bar -1 The total theoretical loading of cellulose nanofibers on the bio-based composite membrane obtained in Example 5 was the same as that in Example 1, but its removal rate of 100 nm diameter polystyrene nanoplastics decreased to 89.8%, while the water flux remained basically the same. The total theoretical loading of cellulose nanofibers on the bio-based composite membrane obtained in Example 3 was 0.112 mg cm⁻¹. -2 It achieves a removal rate of up to 99.6% for polystyrene nanoplastics, with a water flux of 8292.0 L / m³. -2 h -1 bar -1 This demonstrates that the bio-based composite membrane of the present invention maintains a high removal rate while exhibiting a high water flux.
[0046] The bio-based composite membrane of this invention can achieve a near 100% removal rate for polystyrene nanoplastics during filtration, with a maximum water flux of 10766.0 L / m³. -2 h -1 bar -1Comparing the removal rate and water flux in Table 1, it was found that when the total theoretical loading of cellulose nanofibers on the bio-based composite membrane is the same, the filtration performance (removal rate and water flux) of the bio-based composite membrane obtained in Example 5, which has a higher theoretical loading of cellulose nanofibers in the first fiber layer, is lower than that in Example 1, which has a lower theoretical loading of cellulose nanofibers in the first fiber layer.
[0047] Examples 6-9 (for comparison)
[0048] The method for preparing a bio-based composite membrane is basically the same as the method for preparing a bio-based composite membrane in Example 1, except that the concentrations of M, N, X, and the concentrations of the first and second cellulose-based nanomaterial ultrasonic dispersions are different. In this example, the concentration of cellulose nanofibers in both the first and second cellulose-based nanomaterial ultrasonic dispersions is 0.5 wt%.
[0049] A method for removing plastic from water using a bio-based composite membrane is basically the same as the method for removing plastic from water using a bio-based composite membrane in Example 1, except that the bio-based composite membrane is one of the bio-based composite membranes obtained in Examples 6 to 9.
[0050] Table 2 shows the removal rate of polystyrene nanoplastics, water flux, M, N, X, theoretical loading of cellulose nanofibers in the first fiber layer and the theoretical loading of cellulose nanofibers in the second fiber layer of the bio-based composite membranes obtained in Examples 6-9.
[0051] Table 2
[0052]
[0053] As shown in Table 2, the bio-based composite membranes obtained in Examples 6-9 all achieved a 100% removal rate for polystyrene nanoplastics with a diameter of 100 nm. However, their water flux decreased with the increase of the theoretical loading of cellulose nanofibers on the bio-based composite membrane. Compared with the bio-based composite membranes obtained in Examples 1-5, the bio-based composite membranes obtained in Examples 6-9 did not have a significant advantage in terms of water flux.
[0054] Example 10
[0055] A method for removing plastic from water using a bio-based composite membrane involves filtering 5 mL of an aqueous dispersion of plastic through the bio-based composite membrane at -0.09 MPa, obtaining the filtrate, and recording the filtration time t (in hours). The concentration C1 of the plastic in the filtrate is determined using a UV spectrophotometer, and the plastic removal rate and water flux are calculated. The bio-based composite membrane is one of the bio-based composite membranes obtained in Examples 1-3; the aqueous dispersion of plastic is a mixture of polystyrene microplastics and deionized water, and the concentration C0 of the polystyrene microplastics in the aqueous dispersion is 50 mg / L.
[0056] Removal rate (%) = (C0 - C1) / C0;
[0057] Water flux (F) = V / (S × t × P);
[0058] Where S is the effective filtration area (1.77 cm²). 2 P is the negative pressure during the filtration process (0.09 MPa, i.e., 0.9 bar), V is the volume of the plastic aqueous dispersion (5 mL), t is the filtration time (h), and F is the water flux (L m). -2 h -1 bar -1 ).
[0059] In Example 10, the removal rate and water flux of the bio-based composite membranes obtained in Examples 1-3 for polystyrene microplastics are shown in Table 3.
[0060] Table 3
[0061]
[0062] As shown in Table 3, the bio-based composite membranes obtained in Examples 1-3 all achieved a removal rate of over 95% for high concentrations (50 mg / L) of polystyrene microplastics (1 μm in diameter) in the plastic aqueous dispersion, with a maximum water flux of 8706.6 L / m³. -2 h -1 bar -1 This demonstrates that the bio-based composite membrane of the present invention exhibits excellent filtration performance for polystyrene microplastics with a diameter of 1 μm.
[0063] Example 11
[0064] A method for removing plastics from water using a bio-based composite membrane includes: firstly, subjecting a plastic aqueous dispersion to air flotation treatment; using the water collected at the bottom of the air flotation as the flotation effluent; filtering 5 mL of the flotation effluent through the bio-based composite membrane under -0.09 MPa conditions to obtain filtrate and recording the filtration time t (in hours); determining the plastic concentration C1 in the filtrate using an ultraviolet spectrophotometer, and calculating the plastic removal rate and water flux. The bio-based composite membrane is one of the bio-based composite membranes obtained in Examples 1-3; the plastic aqueous dispersion is a mixture of polystyrene microplastics and deionized water, and the concentration C0 of the polystyrene microplastics in the plastic aqueous dispersion is 50 mg / L.
[0065] Removal rate (%) = (C0 - C1) / C0;
[0066] Water flux (F) = V / (S × t × P);
[0067] Where S is the effective filtration area (1.77 cm²). 2 P is the negative pressure during the filtration process (0.09 MPa, i.e., 0.9 bar), V is the volume of water discharged from the flotation process (5 mL), t is the filtration time (h), and F is the water flux (L m³). -2 h -1 bar -1 ).
[0068] The air flotation treatment of the plastic aqueous dispersion includes: suspending the air stone connected to the air outlet pipe of a peristaltic pump (model BT100-2J, purchased from Baoding Lange Constant Flow Pump Co., Ltd.) in the lower part of a beaker, adding 80 mL of the plastic aqueous dispersion to the beaker, turning on the peristaltic pump (speed of 100 rpm), and allowing air to be introduced into the beaker through the air outlet pipe of the peristaltic pump for 1 hour, thus performing air flotation treatment on the plastic aqueous dispersion, and taking 5 mL of liquid below the air stone in the beaker as the air flotation effluent.
[0069] In this embodiment, the removal rate and water flux of the bio-based composite membranes obtained in Examples 1-3 for polystyrene microplastics are shown in Table 4.
[0070] Table 4
[0071]
[0072] As shown in Table 4, the bio-based composite membranes obtained in Examples 1-3 all achieved a removal rate of over 96.5% for high concentrations (50 mg / L) of polystyrene microplastics in the plastic aqueous dispersion, with a maximum water flux of 9432.2 L / m³. -2 h -1 bar -1Comparing the removal rate and water flux data in Tables 3 and 4, it can be seen that when the theoretical loading of cellulose nanofibers on the bio-based composite membrane is the same, pre-treatment of the plastic aqueous dispersion with a peristaltic pump via air flotation can significantly increase the water flux. This indicates that air flotation combined with membrane filtration can further increase the water flux while maintaining a high removal rate, demonstrating excellent removal performance.
[0073] Comparative Examples 1-3
[0074] A method for preparing a composite membrane includes the following steps:
[0075] Step 1: The cellulose nanofiber dispersion is uniformly dispersed in deionized water and sonicated at 40 kHz for 60 min (ultrasound power is 360 W) to mix evenly, so as to obtain a uniformly dispersed first cellulose-based nanomaterial ultrasonic dispersion with a concentration of 0.5 wt% of cellulose nanofibers.
[0076] Step 2: Install the cellulose acetate membrane onto the glass filter (the effective filtration area (S) of the glass filter is 1.77 cm²). 2 On the cellulose acetate membrane, under the condition of -0.09 MPa, the cellulose nanofibers in the ultrasonic dispersion of the first cellulose-based nanomaterials were trapped on the cellulose acetate membrane by vacuum filtration to form the first fiber layer, thus obtaining a composite membrane (single-layer structure).
[0077] The theoretical loading of cellulose nanofibers on the composite membrane is calculated as follows: Theoretical loading of cellulose nanofibers in the first fiber layer = ρ × M × concentration of cellulose nanofibers in the ultrasonic dispersion of the first cellulose-based nanomaterial / S. Where ρ is 1000 mg / cm³. 3 .
[0078] A method for removing plastics from water using a composite membrane includes: filtering 5 mL of an aqueous plastic dispersion through any one of the composite membranes from Comparative Examples 1 to 3 under a pressure of -0.09 MPa, obtaining a filtrate, and recording the filtration time t (in hours); determining the concentration C1 of the plastic in the filtrate using an ultraviolet spectrophotometer, and calculating the plastic removal rate and water flux. The aqueous plastic dispersion is a mixture of polystyrene nanoplastics and deionized water, and the concentration C0 of the polystyrene nanoplastics in the aqueous plastic dispersion is 10 mg / L.
[0079] Removal rate (%) = (C0 - C1) / C0;
[0080] Water flux (F) = V / (S × t × P);
[0081] Where S is the effective filtration area (1.77 cm²). 2P is the negative pressure during the filtration process (0.09 MPa, i.e., 0.9 bar), V is the volume of the plastic aqueous dispersion (5 mL), t is the filtration time (h), and F is the water flux (L m). -2 h -1 bar -1 ).
[0082] The removal rate, water flux, M, and theoretical loading of cellulose nanofibers on the composite membranes obtained in Comparative Examples 1-3 are shown in Table 5.
[0083] Table 5
[0084]
[0085] Table 5 shows that although the composite membrane obtained in Comparative Example 1 showed good removal efficiency for polystyrene nanoplastics, its water flux was relatively low. When the theoretical loading of cellulose nanofibers on the composite membrane was 0.56 mg / cm³, the water flux was significantly reduced. -2 At that time, the composite membrane obtained in Comparative Example 2 achieved a 100% removal rate for polystyrene nanoplastics, with a water flux of only 574.6 L / m³. -2 h -1 bar -1 When the theoretical loading of cellulose nanofibers on the composite membrane is further increased to 0.85 mg cm⁻¹ -2 The water flux of the composite membrane obtained in Comparative Example 3 decreased to 361.6 m³. -2 h -1 bar -1 The low water flux severely limits filtration efficiency. This indicates that composite membranes with a single-layer structure cannot simultaneously achieve high removal rates and high water flux.
[0086] Comparative Example 4
[0087] A method for preparing a composite membrane includes the following steps:
[0088] Step 1: Mix the cellulose nanofiber dispersion with deionized water and stir until homogeneous to obtain the first cellulose-based nanomaterial dispersion (no ultrasonication is performed during the preparation of the first cellulose-based nanomaterial dispersion). The concentration of cellulose nanofibers in the first cellulose-based nanomaterial dispersion is 0.5 wt%.
[0089] Step 2: Install the cellulose acetate membrane onto the glass filter (the effective filtration area (S) of the glass filter is 1.77 cm²). 2 On the cellulose acetate membrane, under the condition of -0.09 MPa, cellulose nanofibers in the first cellulose-based nanomaterial dispersion of M mL were trapped on the cellulose acetate membrane by vacuum filtration to form the first fiber layer, thus obtaining a composite membrane (single-layer structure).
[0090] The theoretical loading capacity of cellulose nanofibers on the composite membrane is calculated as follows: Theoretical loading capacity of cellulose nanofibers in the first fiber layer = ρ × M × concentration of cellulose nanofibers in the first cellulose-based nanomaterial dispersion / S. Where ρ is 1000 mg / cm³. 3 .
[0091] A method for removing plastics from water using a composite membrane includes: filtering 5 mL of an aqueous plastic dispersion through the composite membrane obtained in Comparative Example 4 at -0.09 MPa to obtain filtrate and recording the filtration time t (in hours); determining the concentration C1 of the plastic in the filtrate using an ultraviolet spectrophotometer, and calculating the plastic removal rate and water flux. The aqueous plastic dispersion is a mixture of polystyrene nanoplastics and deionized water, and the concentration C0 of the polystyrene nanoplastics in the aqueous plastic dispersion is 10 mg / L.
[0092] Removal rate (%) = (C0 - C1) / C0;
[0093] Water flux (F) = V / (S × t × P);
[0094] Where S is the effective filtration area (1.77 cm²). 2 P is the negative pressure during the filtration process (0.09 MPa, i.e., 0.9 bar), V is the volume of the plastic aqueous dispersion (5 mL), t is the filtration time (h), and F is the water flux (L m). -2 h -1 bar -1 ).
[0095] The composite membrane obtained in Comparative Example 4 only achieved a 15.5% removal rate for polystyrene nanoplastics with a diameter of 100 nm, far lower than that in Comparative Example 3 (100% removal rate). This indicates that ultrasonic treatment of the cellulose nanofiber dispersion can significantly improve the removal rate of polystyrene nanoplastics by the composite membrane. Therefore, ultrasonic treatment is essential.
[0096] Comparative Example 5
[0097] A bio-based composite membrane with a single-layer structure is the composite membrane obtained in step 2 of Example 3.
[0098] Comparative Example 6
[0099] A method for preparing a bio-based composite membrane with a three-layer structure includes: preparing a third cellulose-based nanomaterial ultrasonic dispersion: uniformly dispersing the cellulose nanofiber dispersion in deionized water, and ultrasonicating at 40 kHz for 60 min (ultrasonic power of 360 W) to mix evenly, thereby obtaining a uniformly dispersed third cellulose-based nanomaterial ultrasonic dispersion, wherein the concentration of cellulose nanofibers in the third cellulose-based nanomaterial ultrasonic dispersion is 0.05 wt%.
[0100] Under -0.09 MPa conditions, cellulose nanofibers in 0.2 mL of the ultrasonic dispersion of the third cellulose-based nanomaterial were trapped on the second fiber layer of the bio-based composite membrane obtained in Example 3 by vacuum filtration to form the third fiber layer, thus obtaining a bio-based composite membrane with a three-layer structure.
[0101] The three-layer structure of the bio-based composite membrane obtained in Comparative Example 6 is arranged in the order of a first fiber layer, a second fiber layer, and a third fiber layer from bottom to top. The theoretical loading of cellulose nanofibers in the first and second fiber layers is the same as in Example 3. The theoretical loading of cellulose nanofibers in the third fiber layer is calculated as follows: Theoretical loading of cellulose nanofibers in the third fiber layer = ρ × 0.2 × concentration of cellulose nanofibers in the ultrasonic dispersion of the third cellulose-based nanomaterial / S. Wherein, ρ is 1000 mg / cm³. 3 .
[0102] The theoretical loading of all cellulose-based nanomaterials on the bio-based composite membrane obtained in Comparative Example 6 (the total theoretical loading of cellulose nanofibers in the three-layer structure) = theoretical loading of cellulose nanofibers in the first fiber layer + theoretical loading of cellulose nanofibers in the second fiber layer + theoretical loading of cellulose nanofibers in the third fiber layer.
[0103] Comparative Example 7
[0104] A method for removing plastic from water using a bio-based composite membrane is basically the same as the method for removing plastic from water using a bio-based composite membrane in Example 3, except that the bio-based composite membrane is one of the bio-based composite membranes obtained in Example 3, Comparative Example 5, and Comparative Example 6.
[0105] Table 6 shows the removal rate, water flux, number of fiber layers, and total theoretical loading of cellulose nanofibers on the bio-based composite membranes obtained in Examples 3, 5, and 6.
[0106] Table 6
[0107]
[0108] As shown in Table 6, the bio-based composite membrane obtained in Comparative Example 5 had a removal rate of only 40.2% for polystyrene nanoplastics with a diameter of 100 nm, while its water flux reached as high as 50305.0 L / m³. -2 h -1 bar -1 When the number of fiber layers on the bio-based composite membrane is 2, the removal rate of polystyrene nanoplastics by the bio-based composite membrane obtained in Example 3 increases to 99.6%, but the water flux decreases significantly. When the number of fiber layers on the bio-based composite membrane is further increased to 3, the removal rate of polystyrene nanoplastics by the bio-based composite membrane obtained in Comparative Example 6 reaches 100%, but the water flux decreases further. This shows that the water flux decreases with the increase of the number of fiber layers. The bio-based composite membrane obtained in Example 3, with its double-layer structure, exhibits the best overall performance, achieving a near 100% removal rate while maintaining a water flux of 8292.0 L / m³. -2 h -1 bar -1 High water flux.
[0109] The preparation method of the bio-based composite membrane of this invention uses inexpensive and readily available biodegradable materials, which greatly reduces production costs and avoids secondary pollution and difficult-to-treat waste. The operation is simple and easy, and it can be applied on a large scale to the purification of drinking water or wastewater. It solves the bottleneck problems of low efficiency, high cost, easy secondary pollution, and difficulty in practical application faced by existing technologies for removing microplastics and nanoplastics from water bodies.
[0110] The present invention has been described above by way of example. It should be noted that any simple modifications, alterations or other equivalent substitutions that can be made by those skilled in the art without creative effort without departing from the core of the present invention fall within the protection scope of the present invention.
Claims
1. A method for removing plastics from water using a bio-based composite membrane, characterized in that, include: Under conditions of -0.1 to -0.08 MPa, a plastic aqueous dispersion is filtered through a bio-based composite membrane, wherein the plastic aqueous dispersion comprises: plastic and water, and the plastic is microplastic and / or nanoplastic; the preparation method of the bio-based composite membrane includes the following steps: Step 1: Prepare a first cellulose-based nanomaterial ultrasonic dispersion by ultrasound. The first cellulose-based nanomaterial ultrasonic dispersion is a homogeneous mixture of cellulose-based nanomaterial and water. Step 2: Under conditions of -0.1 to -0.08 MPa, the cellulose-based nanomaterials in the ultrasonic dispersion of the first cellulose-based nanomaterials are retained on the cellulose acetate membrane by vacuum filtration to obtain a composite membrane, wherein the cellulose-based nanomaterials in the ultrasonic dispersion of the first cellulose-based nanomaterials form a first fiber layer on the cellulose acetate membrane; Step 3: Prepare a second cellulose-based nanomaterial ultrasonic dispersion by ultrasound. The second cellulose-based nanomaterial ultrasonic dispersion is a homogeneous mixture of cellulose-based nanomaterials and water. Under conditions of -0.1 to -0.08 MPa, the cellulose-based nanomaterials in the second cellulose-based nanomaterial ultrasonic dispersion are trapped on the first fiber layer of the composite membrane by vacuum filtration to form a second fiber layer, thus obtaining a bio-based composite membrane. The ultrasound time is 50 to 60 minutes, and the ultrasound frequency is 38 to 42 kHz. The ratio of cellulose-based nanomaterials in the first cellulose-based nanomaterial ultrasonic dispersion to that in the second cellulose-based nanomaterial ultrasonic dispersion is (0.1 to 0.2):(0.1 to 0.2) by mass. The theoretical loading of cellulose-based nanomaterials in the first fiber layer is m1 / S, where m1 is the mass of cellulose-based nanomaterials in the first cellulose-based nanomaterial ultrasonic dispersion, and S is the effective filtration area of the vacuum filtration. The theoretical loading of cellulose-based nanomaterials in the second fiber layer = m2 / S, where m2 is the mass of cellulose-based nanomaterials in the ultrasonic dispersion of the second cellulose-based nanomaterials; The theoretical loading of cellulose-based nanomaterials in the first fiber layer and the sum of the theoretical loading of cellulose-based nanomaterials in the second fiber layer are 0.08~0.12 mg cm⁻¹. -2 ; The concentrations of cellulose-based nanomaterials in the first and second ultrasonic dispersions of cellulose-based nanomaterials are both 0.05~0.2wt%. The length of the cellulose-based nanomaterials is 1~30 μm and the diameter is 1~50 nm. The cellulose-based nanomaterials are cellulose nanofibers.
2. The method according to claim 1, characterized in that, The cellulose acetate membrane has a pore size of 4.75~5.25 μm and a diameter of 24.8~25.2 mm.
3. The method according to claim 1, characterized in that, The methods for preparing the first cellulose-based nanomaterial ultrasonic dispersion and the second cellulose-based nanomaterial ultrasonic dispersion are the same, both including: mixing the cellulose nanofiber dispersion with water and ultrasonicating to mix them evenly.
4. The method according to claim 1, characterized in that, The concentration of plastic in the plastic aqueous dispersion is 10~50 mg / L.
5. The method according to claim 1, characterized in that, Before filtration, the plastic aqueous dispersion is subjected to air flotation treatment.
Citation Information
Patent Citations
Preparation method and application of composite paper-based material for filtering micro-nano plastic
CN118223330A
Preparation method and application of cationized composite paper-based material for filtering nano plastic
CN120819006A
Preparation method of Janus type micro-nano plastic separation membrane based on nano cellulose
CN121155374A
Composite film material with high thermal conductivity and water transmission as well as preparation method and application thereof
CN111518317A
Cellulose fiber-based sandwich structure filter material for removing micro-plastics and preparation method of cellulose fiber-based sandwich structure filter material
CN121648646A
